Cold Water Immersion during Pregnancy: Risk Analysis, Benefits, and Guidelines. A Review of Current Evidence - Kwiatkowska, Anna; Przepióra, Agnieszka; Żmigrodzka, Anna; Orłowska, Maria; Kozłowska, Jana; Sanocka, Maria; Falana, Joanna; Wielogórska, Aleksandra; Trojnar, Karolina; Czernic-Goławska , Klaudia; et al. (Quality in Sport, 2026)
Aim: To review scientific reports and clinical guidelines regarding Cold Water Immersion (CWI) impact on the maternal body and fetal well-being, focusing on vascular, metabolic, and neuroendocrine risk stratification. Material and Methods: Analysis of PubMed, Wiley Online Library, and international expert consensuses was conducted, focusing on CWI in pregnancy, thermal stress physiology, and brown adipose tissue (BAT) adaptation. Results: Research on CWI in pregnancy is limited, necessitating clinical caution. Safety depends on pre-conception cold adaptation. In adapted women, CWI promotes beneficial hematological changes and insulin sensitivity (BAT activation). Identified risks include third-trimester aortocaval compression syndrome (ACCS) and "autonomic conflict" inducing arrhythmias. Current consensus advises against CWI initiation during pregnancy for novices due to catecholamine release and fetal hypoxia risks. Conclusions: CWI in pregnancy is permissible only as a continuation of long-term pre-conception practice, without obstetric or cardiac contraindications. It requires medical supervision, 50% immersion time reduction, and safety protocols (no head submersion). Correct implementation in adapted women supports maternal vascular resilience and programs neonatal metabolism via BAT stimulation, improving glycemic stability and thermogenesis after birth.